Arsitektur Masjid Raya Baiturrahman Banda Aceh: Representasi Politik Dan Selera Penguasa - Abdul Jalil, Laila; Hasrianti; Manalu, Mifani S; Wibowo, Andreas Satria (PURBAWIDYA, 2026)
Baiturrahman Grand Mosque is one of the historic mosques located in the center of Banda Aceh City. During the Aceh War against Dutch colonialism, the mosque was burned down. As an effort to quell the anger of the Acehnese people, the Dutch rebuilt the Baiturrahman Grand Mosque in a new architectural style that featured a dome, which later became a milestone in modern mosque architecture in Aceh. This research methodology uses a historical, architectural, and political approach. This approach is used to observe the development of the architecture of the mosque over time, exploring information about the mosque’s architecture from various perspectives, including cultural characteristics and the political reasons behind its construction. The purpose of this study is to examine the representation of the rulers’ tastes in mosque architecture and the political motives behind the construction of mosques. . The study revealed that mosque architecture has undergone a transformation from traditional to modern forms, influenced by various political interests and reflecting the architectural preferences of rulers from its inception to the post-independence period . The construction of mosques served political purposes: to demonstrate royal identity and the presence of Muslim communities, to garner sympathy, to control public activities, and to strengthen the image of the leadership.